The continuum of ovarian response leading to birth, a real world study of ART in Spain - M. Ferrando; B. Coroleu; L. Rodríguez-Tabernero (Publishing House TRILIST, 2021)
Background. The first biosimilar of recombinant follicle stimulating hormone (rFSH) launched in Europe was Bemfola® in 2014 following a clinical development programme demonstrating efficacy and safety to the satisfaction of the European Medicines Agency. Since then the increasing use of biosimilar rFSH has provided the opportunity to study both effectiveness across the whole population and the variation of rFSH use during routine clinical care in a real-world setting in Spain. Methods. This is a real-world study of 1222 women treated in 26 assisted reproduction treatment centres throughout Spain providing experience of the use of a biosimilar recombinant follicle stimulating hormone in four distinct populations. The four populations studied were poor responders, suboptimal responders, normal responders and oocyte donors. The primary endpoint was the total number of oocytes retrieved. Secondary endpoints included number of days of rFSH stimulation, total dose of rFSH administered, number of MII oocytes, number of fertilized oocytes, quality of embryos, number of embryos transferred, implantation rates, clinical pregnancy rates following embryo transfer, number of multiple pregnancies and number of serious adverse reactions, including moderate-to-severe OHSS. Results. Differences were seen across the populations both in the characteristics of the women and ART outcomes suggestive of a continuum of fertility prognosis. In the poor responders, suboptimal responders, normal responders and oocyte donor populations the mean age in years was 39.9 (±SD 3.4), 38.4 (±SD 2.9), 34.4 (±SD 3.3) and 26 (±SD 4.6) respectively and number of oocytes retrieved was 4.1 (±SD 2.7), 8.6 (±SD 6.0), 12.2 (±SD 7.2) and 19.5 (±SD 9.5) respectively. The proportion of embryos graded as best quality was 18.5%, 33.0% and 43.8%, and graded as worst quality was 20.4%, 5.8% and 5.8% for poor responders, suboptimal responders and normal responders respectively. In a similar pattern, for poor responders, suboptimal responders and normal responders the implantation rates were 16.0%, (8/50), 22.4% (49/219), 30.6% (97/317) respectively and clinical pregnancy rates were 23.2% (10/43), 30.4% (59/194) and 37.0% (114/308) respectively. Adverse events were reported in only 7 of 1222 women (0.6%). Conclusion. Overall the results were consistent with the national ART results reported for Spain, hence this study provides reassurance of the clinical effectiveness of a biosimilar rFSH used in a real world setting.